Analisis Drug Related Problem Terkait Dosis pada pasien Balita dengan Diagnosis Diare di Puskesmas Lumpatan Kabupaten Musi Banyuasin Periode Januari-Maret 2018 - Eka Afrika; Helni Anggraini; Muhammad Romadhon; Satra Yunola (Universitas Batanghari Jambi, 2020)
Diarrheal disease is an endemic disease in Indonesia and is also a potential illness of Extraordinary Occurrence (KLB) which is often accompanied by death. Puskesmas Lumpatan of Musi Banyuasin Regency which is one of the public health centers in Musi Banyuasin district where the number of samples in this study is 20 patients including 7 male patients and 13 female patients. Toodler patients with Neonate age (0-1 months) were 0 patients, in infants (1 month-2 years) as many as 14 patients while children (2 years-5years) were 6. The number of children under-five patients who received oralitic treatment were 4 patients, zinc as many as 11 patients and cotrimoxazole as many as 15 patients, where there are drug-related problems only at the drug delivery that is too low the zinc drug is 9,10%